2018
DOI: 10.3389/fmicb.2018.02802
|View full text |Cite
|
Sign up to set email alerts
|

Improved Microbial Safety of Direct Ozone-Depurated Shellstock Eastern Oysters (Crassostrea virginica) by Superchilled Storage

Abstract: The effect of superchilled storage at -1°C on the microbial safety of oyster depurated with 0.2, 0.4, and 0.6 mg/L ozone was studied for 14 days. Fecal coliforms (4,100–16,000 MPN/100 g), Escherichia coli (1,500–3,650 MPN/100 g), Vibrio cholerae non-O1/non-O139 (13.0–102.0 MPN/g), and Salmonella spp. (2.270–3.035 × 103 CFU/g) were initially present in raw oysters. After 6 h depuration, fecal coliform counts decreased (P < 0.05) to 300, 20 and 20 MPN/100 g for 0.2, 0.4, and 0.6 mg/L treatments, while a 0.3 log … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Though some studies detail the use of ozone on other bacteria in depurating oysters, very few studies have demonstrated the effects of ozone on the reduction of VV and VP in oysters (López Hernández et al., 2018). One study, however, effectively reduced Vibrio cholerae in oysters from 26.5 ± 0.7 to <0.3, 13.5 ± 0.7 to <0.3, and 15.5 ± 0.7 to <0.3 MPN/g, respectively.…”
Section: Modes Of Disinfection For Oyster Depuration Systemsmentioning
confidence: 99%
“…Though some studies detail the use of ozone on other bacteria in depurating oysters, very few studies have demonstrated the effects of ozone on the reduction of VV and VP in oysters (López Hernández et al., 2018). One study, however, effectively reduced Vibrio cholerae in oysters from 26.5 ± 0.7 to <0.3, 13.5 ± 0.7 to <0.3, and 15.5 ± 0.7 to <0.3 MPN/g, respectively.…”
Section: Modes Of Disinfection For Oyster Depuration Systemsmentioning
confidence: 99%
“…Considering this finding, we used purified nonpathogenic (Vp-tlh) and pathogenic (Vp-tdh) strains isolated from the live shellstock oysters for RT-PCR amplification in vitro due to the high endogenous bacterial loads found in live shellstock oysters harvested from Veracruz lagoons. We have previously reported that the fecal coliform, E. coli, and V. cholerae non-O1/nonO139 levels do not decrease to zero in live shellstock oysters (C. virginica), even with artificial seawater or ozonated seawater depuration [43]. Therefore, to determine the relationship of the expression of the rpos and cspA genes on the survival of purified (Vp-tlh) and (Vp-tdh) strains, the expression of both genes was monitored in vitro during the storage period at 7 • C. Figure 3a,b show the average expression of the rpos and cspA genes from the V. parahaemolyticus strains for 216 h of storage at 7 • C. Figure 3a shows that the average relative expression of the rpoS gene of the (Vp-tlh) strains on day 0 decreased (p > 0.05) after 24 h. However, the rpoS gene transcript levels at 0 h were not significantly different (p > 0.05) from those observed at 72, 120, 168, and 216 h. rpoS gene expression was repressed by −0.024-fold after 24 h. Meanwhile, the relative cspA gene expression at 0 h increased significantly (p < 0.05) after 24 h, remaining relatively constant (p > 0.05) during the storage period.…”
Section: Effect Of Cold Shock On Gene Expression Of Nonpathogenic (Vpmentioning
confidence: 95%
“…Another issue facing the seafood commerce is the possibility of health risk posed by oyster consumption, since most bivalves are consumed raw or minimally cooked, and whole, including the viscera, rendering the bivalves a risky group of food. López Hernández et al (2018) worked in this regard to study the effect of oyster depuration with 0.2, 0.4, and 0.6 mg/L ozonated artificial seawater, super-chilled, and stored at −1 • C on the microbial safety of oyster. It was found that ozone treatment for 6 h at 0.4 mg/L AO efficiently decreased fecal coliforms, E. coli, Salmonella, and V. cholerae counts in oysters and super-chilled storage enhanced disinfection efficiency and microbiological quality of oysters for approximately 9 days.…”
Section: Seafood Decontaminationmentioning
confidence: 99%
“…The oxidation of membrane glycoproteins and/or glycolipids also occurs (Ersoy et al., 2019). Added to this, ozone inhibits membrane‐bound enzymes as well as damages DNA because of the oxidation of double bonds by singlet oxygen (López Hernández et al., 2018). The deterioration of cell walls leads to cell lysis and, finally, cell death (Ersoy et al., 2019).…”
Section: Mechanism Of Microbial Inactivation By Aqueous Ozonementioning
confidence: 99%
See 1 more Smart Citation